2018
DOI: 10.1029/2018jb015995
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Azimuthal Anisotropy Beneath the Southeastern Tibetan Plateau and its Geodynamic Implications

Abstract: The fast orientation and magnitude of crustal azimuthal anisotropy beneath the southeastern Tibetan Plateau and adjacent areas are measured by analyzing the sinusoidal moveout of the P to S converted phase from the Moho. Beneath the tectonically active plateau, the mean magnitude is 0.48 ± 0.13 s, which is about twice as large as that observed in the stable Sichuan Basin (0.23 ± 0.10 s). The two areas are separated by the Longmenshan fault zone, a zone of devastating earthquakes including the 12 May 2008 MW 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 87 publications
12
52
0
Order By: Relevance
“…In contrast, the fast orientations for the upper and lower layers measured at five stations in the Zhangjiakou-Penglai Fault Zone are significantly different ( Figure 6). This nearly 90 • flip of the fast orientations is also found by direct S splitting from local events conducted in the Zhangjiakou-Penglai Fault Zone and active fault zones in Iceland (Crampin et al, 2002), as well as P m s moveout in the eastern Tibetan Plateau (Kong et al, 2016;Zheng et al, 2018). The 90 • difference between the fast orientation of the upper and lower layers could be caused by complex crustal structure beneath the fault zone with a broad shear zone at depth.…”
Section: Formation Mechanisms Of the Observed Crustal Anisotropy 61supporting
confidence: 57%
See 2 more Smart Citations
“…In contrast, the fast orientations for the upper and lower layers measured at five stations in the Zhangjiakou-Penglai Fault Zone are significantly different ( Figure 6). This nearly 90 • flip of the fast orientations is also found by direct S splitting from local events conducted in the Zhangjiakou-Penglai Fault Zone and active fault zones in Iceland (Crampin et al, 2002), as well as P m s moveout in the eastern Tibetan Plateau (Kong et al, 2016;Zheng et al, 2018). The 90 • difference between the fast orientation of the upper and lower layers could be caused by complex crustal structure beneath the fault zone with a broad shear zone at depth.…”
Section: Formation Mechanisms Of the Observed Crustal Anisotropy 61supporting
confidence: 57%
“…Such a spatial variation is consistent with results from a direct S splitting study (Gao et al, ), which shows that the average delay time in the central part of the fault zone is greater than 5 ms/km, whereas that in the area away from the fault is generally less than 3 ms/km. The inverse relationship between the δt measurements and the distance to the center of the fault zone, when combined with the observation that the fast orientations at the stations closest to the fault zone are parallel or subparallel to the strike of the fault zone (Figure ), may indicate a gradual intensification of fluid‐filled fractures toward the center of the active fault zone (Kong et al, ; Zheng et al, ). An alternative mechanism for the enhanced anisotropy along the fault zone is a broad zone of viscous deformation in the middle to lower crust, and a narrow zone of fluid‐filled fractures in the upper crust (e.g., Burgmann & Dresen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pn waves travel mostly in the uppermost mantle, and therefore, the resulting azimuthal anisotropies are from the uppermost mantle. Pms phases from different directions can also be fitted with cosine functions to obtain the azimuthal anisotropies beneath stations (Sun et al, 2012; Sun et al, 2015; Zheng et al, 2018). Surface wave dispersions are the most widely used data to extract azimuthal anisotropies for different periods (Ceylan et al, 2012; Legendre et al, 2015; Su et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, joint analysis of GPS and SKS/SKKS splitting results shows that deformations in the crust and mantle are largely coupled in the eastern Tibetan Plateau, which is inconsistent with the predictions of the lower crust flow model (Chang et al, 2015; León Soto et al, 2012; Sol et al, 2007; Wang et al, 2008; Yang et al, 2018). On the other hand, based on anisotropies from Pms phases, some studies (Kong et al, 2016; Sun et al, 2012; Sun et al, 2015; Zheng et al, 2018) have suggested the existence of a lower crust flow in the region. Chen et al (2013) argued that a midlower crust flow may exist beneath the interior of the eastern Tibetan Plateau, but block extrusion resulting from pure shearing may occur in the Central Yunnan subblock.…”
Section: Introductionmentioning
confidence: 99%